ANALYSIS OF THE EFFECT OF VALUE-ADDED TAX IMPLEMENTATION ON TAX REVENUE AT KPP PRATAMA KEDIRI - Tika, Hella Laras; Srikalimah, Srikalimah; Suaidah, Imarotus (Penelitian dan Pengembangan Ilmu, 2025)
This study analyzes the impact of the implementation of Value Added Tax (VAT) on tax revenue at the Pratama Tax Office in Kediri. The method used is descriptive qualitative, employing document analysis and interviews with entrepreneurs, consultants, and tax officers. The results indicate that the implementation of VAT significantly contributes to tax revenue, but varying levels of understanding among Taxable Entrepreneurs (PKP) pose major challenges. The increase in the VAT rate from 10% to 12% has the potential to reduce purchasing power, especially among low-income groups. This study is consistent with previous findings that indicate an increase in VAT rates can enhance state revenue but may also risk decreasing consumption. It is recommended that the Pratama Tax Office in Kediri enhance tax education programs and enforce stricter compliance monitoring to raise PKP awareness. Thus, it is hoped that VAT revenue can be optimized and support sustainable economic growth.